Phytochemical screening and study of analgesic potential of Pandanus fascicularis different root extract in experimental animal model - Asha, Saima Zaman (BRAC University, 2017)
This project report is submitted in a partial fulfillment of the requirements for the degree of Bachelor of Pharmacy, 2016